A Study On The Prevalence Of Amphetamine-Type-Stimulants (Ats) Use Among Primary And Private Methadone Maintenance Treatment (Mmt) Clients In Kuantan, Pahang - Mamat, Ruzmayuddin (2019)
Optimum prescription of methadone dose is associated with improved treatment compliance. The use of amphetamine-type-stimulants (ATS) (e.g. methamphetamine and amphetamine) during Methadone Maintenance Treatment (MMT) is associated with poor treatment compliance and risky HIV behaviours. This study aims to investigate the relationship between methadone dose and prevalence of ATS use among clients enrolled in primary and private MMT program in Kuantan, Pahang. A total of two hundred and thirty-seven (n=129 primary and n=108 private) methadone users were recruited from two MMT programs through convenience sampling for this cross-sectional study. The surveys were conducted through face-to-face interviews with a semi-structured questionnaire. All the respondents were screened for illicit drug use. Majority males (97%, n=230/237), only 7 were females, while most were Malays (96%, n= 228/237). Half (50%, n=119/237) were between the age of 18 to 37 years, 47% single (n=112/237), and 83% (n=198/237) employed. Twenty-nine percent (n=70/237) had hepatitis C. The samples mean age of first methadone use was 32.8 years, mean duration of methadone treatment was 48.86 months and average methadone dose was 52.78mg/daily. Two-thirds (68%, n=161/237) had ≤4 years methadone treatment history, while 32% (n=76/237) have used methadone >4 years. Fifty-five percent (n=130/237) received ≤50mg of methadone dose daily and 45% (n=107/237) received >51mg/daily of methadone dose. One-third (36%, n=86/237) used ATS between 1-3 days and 26% (n=61/237) used ATS >4 days in the last 7 days.